621 Polymorphic Length of Foxe1 Alanine Stretch in Isolated Cleft Lip and/or Palate. (October 2012) - Hsiao, HP; Lin, HH; Chen, CY; Chen, BH; Chao, MC
Abstract : Background and Aim: Isolated cleft lip with/or cleft palate (CL/P) is a common complex birth defect that varies in prevalence with Asian and Amerindian ancestry having the highest rates. While several genes had significant association to the CL/P, the FOXE1 gene is involved in embryonic formation and is expressed in the secondary palate epithelium in human fetus. Since the first description of FOXE1 mutation found in cases of cleft palate, thyroid agenesis and choanal atresia, Moreno had conducted a genome-wide scan for CL/P patients and confirmed the highly linkage to the 9q23–33, which resided the potential FOXE1 . Herein, we are trying to investigate the isolated CL/P in Taiwan to see whether the polymorphic length of FOXE1 play an important role in the palatogenesis. Method: Eighty patients with isolated CL/PCL/P and one hundred controls were recruited in the study. Genomic DNA was amplified by PCR the amplicons containing polyalanine tract (234 to 258 bp; 11–19 alanines) were purified, then directly sequenced. Results and conclusion: The 14/14 genotype in polymorphic alanine stretch was most frequent both in cases (98.7%) and in controls (98.0%), whereas the heterozygous 14/16 accounted for one case and two controls. The 14 alanine strech accounts for the major allele frequency of the polymorphic length in FOXE1 which consists of the high frequency in previous report from Japan. Although CL/P patients was linked to FOXE1, the polymorphic FOXE1 alanine stretch has no association with isolated CL/P in Taiwan. It appears to reflect the heterogeneity in formation of CL/P, perhaps a population difference.